Super-hydrophilic / super-aerophobic electrocatalyst Co-Cu-P for fully decomposing water and preparation method of super-hydrophilic / super-aerophobic electrocatalyst Co-Cu-P
By doping Cu elements into the CoP electrocatalyst, the problem of slow catalytic kinetics of CoP under alkaline conditions is solved, efficient hydrolysis of hydrogen catalysis is achieved, and the hydrogen production efficiency of the catalyst is improved.
Patent Information
- Application Number
- CN202510056399.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-11
AI Technical Summary
The adsorption and dissociation of water by existing CoP electrocatalysts under alkaline conditions and slow desorption of gas products have limited their wide application.
By doping Cu elements, the bimetallic phosphide Co-Cu-P with high hydrophilicity and more exposed active sites is constructed, reducing the dissociation energy barrier of water, optimizing the adsorption of intermediates, and improving the hydrogen production efficiency of the catalyst.
High-efficiency catalysis under alkaline conditions is achieved, the hydrogen production efficiency of the catalyst is improved, the dissociation energy barrier of water is reduced, the adsorption of intermediates is optimized, and a high mass transfer kinetic electrocatalyst is formed.
Smart Images

Figure CN119793499A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water electrolysis catalysts, and specifically relates to a super-hydrophilic / super-aerophobic electrocatalyst Co-Cu-P for complete water splitting and a preparation method thereof. Background Art
[0002] In order to reduce dependence on fossil fuels and greenhouse gas emissions, it is urgent to develop sustainable energy conversion technologies and clean energy carriers. Hydrogen, as a carbon-free green energy carrier, has a high specific capacity and is considered to be one of the most promising alternatives for future energy. At present, the large-scale production of hydrogen mainly relies on the steam reforming reaction of fossil resources, which further aggravates the depletion of fossil fuels and the greenhouse effect. Compared with steam reforming hydrogen production, water electrolysis hydrogen production technology uses water as a reactant, has the advantages of not releasing greenhouse gases and significant hydrogen production efficiency, and is widely regarded as a sustainable hydrogen production method.
[0003] Transition metal phosphides are considered to be the most promising catalysts for water electrolysis due to their excellent properties. CoP has attracted considerable attention due to its excellent conductivity, multi-redox properties and hybrid d orbitals. Unfortunately, under alkaline conditions, the adsorption and dissociation of water by CoP and the sluggish product desorption kinetics limit its widespread application. Summary of the invention
[0004] The purpose of the present invention is to provide a super-hydrophilic / super-aerophobic electrocatalyst Co-Cu-P for complete water splitting and a preparation method thereof. The present invention enables the electrocatalyst to solve the problems of water adsorption and dissociation by the electrocatalyst and sluggish desorption kinetics of gas products under alkaline conditions by designing the electrocatalyst structure.
[0005] To achieve the above object, the technical solution adopted by the present invention is: A superhydrophilic / superaerophobic electrocatalyst Co-Cu-P for overall water splitting, wherein the molecular formula of the electrocatalyst Co-Cu-P is Co x Cu 1-x P, 0≤x<1, the structure is sea urchin-like nanoflower or granular pearl ball.
[0006] Furthermore, the molecular formula of the electrocatalyst Co-Cu-P is preferably Co 0.95 Cu 0.05 P, the structure is a sea urchin-like nanoflower composed of nanoneedles grown on carbon cloth.
[0007] A method for preparing a super-hydrophilic / super-aerophobic electrocatalyst Co-Cu-P for overall water splitting comprises the following steps: (1) Dissolve cobalt nitrate hexahydrate, copper nitrate trihydrate, ammonium fluoride, and urea in deionized water and stir at room temperature for 30 minutes until a transparent mixed solution is formed; (2) transferring the carbon cloth and the mixed solution to a polytetrafluoroethylene reactor for hydrothermal reaction. After the hydrothermal reaction is completed, cooling, washing with deionized water and anhydrous ethanol, and drying to prepare a precursor; (3) Weigh sodium hypophosphite, place the precursor and sodium hypophosphite in a magnetic boat, respectively located upstream and downstream of a tubular furnace, and calcine under argon conditions. After calcination, collect the product to obtain the electrocatalyst Co-Cu-P.
[0008] Furthermore, in step (1), the concentration of ammonium fluoride is 0.1-0.2 mol / L, and the concentration of urea is 0.15-0.20 mol / L.
[0009] Furthermore, in step (1), Co 2+ , Cu 2+ The total concentration of Co-Cu-P is 0.01-0.05 mol / L. The sum of the stoichiometric numbers of Co and Cu in Co-Cu-P is 1. x Cu 1-x The stoichiometric number of Co in P is x=0, 0.50, 0.83, 0.90, 0.94, 0.95, 0.97, 1.00.
[0010] Furthermore, in step (1), the concentration of ammonium fluoride is preferably 1 mmol / 7.5 mL, the concentration of urea is preferably 11 mmol / 60 mL, and the concentration of Co 2+ , Cu 2+ The total concentration of is preferably 1 mmol / 30 mL, and the molar ratio of Co to Cu is 0.95:0.05.
[0011] Furthermore, the hydrothermal reaction in step (2) is carried out at 100-150° C. for 8-16 h. This step is mainly to form a Co-Cu precursor on the carbon cloth, and at the same time, a sea urchin-shaped nanoflower structure morphology appears.
[0012] Furthermore, the hydrothermal reaction in step (2) is preferably carried out at 120° C. for 12 h.
[0013] Furthermore, in step (3), the molar ratio of sodium hypophosphite to the precursor is 10:1.
[0014] Furthermore, the calcination conditions in step (3) are 1-3°C·min −1 The temperature is raised to 200-500°C at a heating rate and kept at this temperature for 1-2 h.
[0015] Furthermore, the calcination conditions in step (3) are preferably 2°C·min−1 The temperature was raised to 300 °C at a heating rate of 100 °C and kept at this temperature for 2 h.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention constructs a bimetallic phosphide with high hydrophilicity and more exposed active sites through the method of doping with transition metal element Cu, reduces the dissociation barrier of water, optimizes the adsorption of intermediates, and improves the hydrogen production efficiency of the catalyst, which can provide a feasible preparation route for the formation of an integral high mass transfer kinetic electrocatalyst.
[0017] 2. The present invention prepares Cu-doped CoP catalysts of different morphologies. When the copper content is less than 33%, sea urchin-like nanoflowers composed of nanoneedles are formed, each flower is 10 microns, and the diameter of a single nanowire is 100 nanometers. When the copper content is greater than 33%, granular pearl balls are formed.
[0018] 3. The present invention realizes the regulation of the super-wettability (combination of super-hydrophilic and super-aerophobic properties) structure of non-precious metal phosphides themselves, further realizes an efficient structure-activity relationship in the process of electrocatalytic water splitting, and provides a feasible experimental and production route for high-performance electrocatalytic water splitting. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The SEM images and corresponding wettability test images of the electrocatalysts with different morphologies prepared in Example 1 and Example 2, wherein a, b, and c are SEM images and corresponding wettability test images of the carbon cloth; d, e, and f are SEM images and corresponding wettability test images of the electrocatalyst prepared in Example 1; g, h, and i are SEM images and corresponding wettability test images of the electrocatalyst prepared in Example 2; Figure 2 is the X-ray diffraction pattern ( Figure 2 a) Scanning electron microscope image ( Figure 2 b and Figure 2 c) Transmission electron microscopy images ( Figure 2 d. Figure 2 e Figure 2 f) Overall STEM image of nanowires ( Figure 2 g), element distribution diagram ( Figure 2 h -2k are the distribution diagrams of Co, Cu, P and O elements on the nanowire); Figure 3 is the electrocatalytic performance of different catalysts, among which, Figure 3 a is the polarization curve of HER, Figure 3 b is the Tafel slope graph, Figure 3 c is the double layer capacitance diagram, Figure 3 d is the it curve graph, Figure 3 e is the comparison with the literature reports, Figure 3 f is the polarization curve of OER, Figure 3 g is the Tafel slope of OER, Figure 3 h is the iT curve of OER; Figure 4 The electrocatalytic performance of the electrocatalyst Co-Cu-P under HER reaction with different Cu doping amounts is shown in Figure 2. Figure 4 a is Co x Cu 1- x LSV curves of HER reaction on P / CC surface (x=0.5, 0.83, 0.90, 0.94, 0.97), Figure 4 b is 10 mA·cm -2 Comparison of overpotentials of HER reactions on different catalyst surfaces at different current densities (Pt / C / CC, Co 0.95 Cu 0.05 P / CC, CoP / CC, Cu3P / CF, CC), Figure 4 c is 10 mA cm -2 Effect of different Cu doping amounts on Co x Cu 1-x Comparison of overpotentials of HER reactions on P / CC surfaces (x=0.5, 0.83, 0.90, 0.94, 0.97). Figure 4 d is Co x Cu 1-x LSV curves of P / CC (x=0.5, 0.83, 0.90, 0.94, 0.95, 0.97, 1) and Nyquist plot of Cu3P / CF; Figure 5 The electrocatalytic performance of the electrocatalyst Co-Cu-P with different Cu doping amounts in the OER reaction. Figure 5 a is Co x Cu 1- x LSV curves of OER reaction on P / CC surface (x=0.5, 0.83, 0.90, 0.94, 0.97), Figure 5 b is 10 mA·cm -2 Comparison of overpotentials of OER reactions on different catalyst surfaces at different current densities (Pt / C / CC, Co 0.95 Cu 0.05 P / CC, CoP / CC, Cu3P / CF, CC), Figure 5 c is 10 mA·cm -2 Effect of different Cu doping amounts on Co x Cu 1-xComparison of overpotentials of OER reactions on P / CC surfaces (x=0.5, 0.83, 0.90, 0.94, 0.97). Figure 5 d is Co x Cu 1-x LSV curves of P / CC (x=0.5, 0.83, 0.90, 0.94, 0.95, 0.97, 1) and Nyquist diagram of Cu3P / CF. DETAILED DESCRIPTION
[0020] The technical solution and effects of the present invention are further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto. Example 1
[0021] The molecular formula of the superhydrophilic / superaerophobic electrocatalyst Co-Cu-P for overall water splitting prepared in this embodiment is Co 0.95 Cu 0.05 P, the preparation process is: (1) Dissolve 1.9 mmol of cobalt nitrate hexahydrate, 0.1 mmol of copper nitrate trihydrate, 8 mmol of ammonium fluoride, and 11 mmol of urea in 60 mL of deionized water and stir at room temperature for 30 min until a transparent mixed solution is formed; (2) transferring the carbon cloth and the mixed solution to a polytetrafluoroethylene reactor for hydrothermal reaction at 120°C for 12 h. After the hydrothermal reaction, cooling, washing with deionized water and anhydrous ethanol, and drying at 60°C for 2 h to prepare a precursor; (3) Sodium hypophosphite (20 mmol in this example) was weighed in a ratio of 10:1 between the amount of sodium hypophosphite and the precursor. The precursor and sodium hypophosphite were placed in a magnetic boat, respectively located upstream and downstream of a tube furnace, and calcined under argon gas at 2 °C / min. −1 The temperature was raised to 300 °C at a heating rate of 1.5 °C and kept at this temperature for 2 h. After the calcination, the product was collected to obtain the electrocatalyst Co 0.95 Cu 0.05 P. Example 2
[0022] The molecular formula of the superhydrophilic / superaerophobic electrocatalyst Co-Cu-P for overall water splitting prepared in this embodiment is Co 0.83 Cu 0.17 P, the preparation process is: (1) Dissolve 1.66 mmol of cobalt nitrate hexahydrate, 0.34 mmol of copper nitrate trihydrate, 8 mmol of ammonium fluoride, and 11 mmol of urea in 60 mL of deionized water and stir at room temperature for 30 min until a transparent mixed solution is formed; (2) transferring the carbon cloth and the mixed solution to a polytetrafluoroethylene reactor for hydrothermal reaction at 120°C for 12 h. After the hydrothermal reaction, cooling, washing with deionized water and anhydrous ethanol, and drying at 60°C for 2 h to prepare a precursor; (3) Sodium hypophosphite (20 mmol in this example) was weighed in a ratio of 10:1 between the amount of sodium hypophosphite and the precursor. The precursor and sodium hypophosphite were placed in a magnetic boat, respectively located upstream and downstream of a tube furnace, and calcined under argon gas at 2 °C / min. −1 The temperature was raised to 300 °C at a heating rate of 1.5 °C and kept at this temperature for 2 h. After the calcination, the product was collected to obtain the electrocatalyst Co 0.83 Cu 0.17 P.
[0023] like Figure 1 As shown, the electrocatalyst Co prepared in Example 1 0.95 Cu 0.05 The morphology of P is a sea urchin-like nanoflower composed of nanoneedles. Each nanoflower has countless single nanoneedles growing radially from the inside to the outside, with a diameter of 10-12 microns. 0.83 Cu 0.17 The morphology of P is granular pearl balls. x Cu 1-x The morphology of P is related to the copper content. When the copper content is high, a pearl-shaped sample composed of nanoparticles is formed, and when the copper content is low, a flower-shaped array is formed. Each nanoflower has countless single nanoneedles that grow radially from the inside to the outside, with a diameter of 10-12 microns. The inventors found that when the Cu content reaches 0.5, the sea urchin shape disappears.
[0024] The hydrophilicity and contact angle of underwater bubbles of electrocatalysts with different morphologies were also tested. Figure 1 c. Carbon cloth itself is hydrophobic, and its hydrophilicity will change after loading Co-Cu-P. The contact angle of water on the surface of the sea urchin-like nanoflower is 0 degrees, and the contact angle of underwater bubbles is 151 degrees, indicating that it has super hydrophilic and super aerophobic properties; while the pearl spherical Co 0.83 Cu 0.17The contact angle of water on the P surface is about 43.6°, indicating that the hydrophilicity is weakened relative to the sea urchin-like nanoflower structure, while the underwater bubble contact angle is 142°, indicating that its air repellency is also weakened relative to the sea urchin-like nanoflower structure; Co-P shows that the water droplet contact angle is greater than 90°, indicating hydrophobicity, and the bubble contact angle is less than 90°, indicating air affinity, showing an amorphous nanowire array morphology. It can be seen that the wettability of the electrocatalyst surface is also related to the morphology. The bubble contact angle of the electrocatalyst with a sea urchin-like nanoflower structure is about 151°, which is greater than the pearl ball sample and carbon cloth. It shows that the electrocatalyst with a sea urchin-like nanoflower structure has superhydrophilic properties.
[0025] Figure 2 The electrocatalyst Co prepared in Example 1 0.95 Cu 0.05 X-ray diffraction pattern of P ( Figure 2 a) Scanning electron microscope image ( Figure 2 b and Figure 2 c) Transmission electron microscopy images ( Figure 2 d. Figure 2 e Figure 2 f) Overall STEM image of nanowires ( Figure 2 g). Figure 2 a The crystal structure of the obtained sample was confirmed, and the peaks at 31.6°, 36.3°, 46.2°, 48.1°, 52.3°, and 56.8° were assigned to the 011, 111, 112, 211, 211, 103, and 301 crystal planes of CoP PDF#29-0497. Figure 2 b and Figure 2 c It can be seen that the electrocatalyst Co prepared in Example 1 0.95 Cu 0.05 P has the morphology of a nanoflower array composed of single nanoneedles, evenly covered on the carbon cloth, and the conical nanowire fractal array is in the form of a nanoflower with a diameter of 15-20μm, growing from the inside out. Figure 2 d. Figure 2 e. Figure 2 f and Figure 2 g It can be seen that the diameter of a single nanowire is 100 nm.
[0026] The hydrogen production performance of different catalysts was tested: a carbon rod was used as the counter electrode, a calomel electrode was used as the reference electrode, and the prepared catalyst was used as the working electrode to form a three-electrode system. The hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) activities of the electrocatalyst were tested in a 1 mol / L KOH solution. Figure 3 The experimental results show that when the copper doping amount is 1.7%, the electrocatalyst Co 0.95 Cu 0.05 P has the best performance at 10 mA·cm -2When 0.95 Cu 0.05 The overpotential of HER of P is 42 mV, the overpotential of OER is 227 mV, and the voltage of complete water splitting is 1.52 V, which exceeds commercial Pt / C and RuO2. Further theoretical calculations show that the doped Cu optimizes the electronic structure of Co and P, reduces the dissociation barrier of water, and makes the Gibbs free energy of hydrogen adsorption close to 0 eV. In the OER process, the reaction energy barrier is reduced, which is conducive to the OER reaction. After doping with Cu, the d-band center of CoP moves up, and the distribution of electrons at the Fermi level also increases significantly, making it easier to produce strong electronic coupling with water, accelerating the transfer of protons, enhancing the adsorption of water, and improving the conductivity of the catalyst, thereby improving the catalytic efficiency of the electrocatalyst.
[0027] The Fe element, which has a smaller electronegativity than Cu, was selected to optimize the electronic structure of CoP. Cobalt-iron layered double hydroxide was synthesized on carbon cloth by hydrothermal method and then further phosphated at low temperature to prepare Co x Fe 1-x P nanostructure, and the optimal iron doping amount is determined by adjusting the Fe ratio. x Fe 1-x P was electrochemically tested in 1 M KOH solution. 0.75 Fe 0.25 P has the best HER and OER activities at 10 mA·cm -2 At a current density of 1.3 Å, the overpotential of HER is only 52 mV, and the overpotential of OER is 260 mV, corresponding to a Tafel slope of 52.1 mV·dec. -1 and 65 mV·dec -1 . 0.75 Fe 0.25 P was used as cathode and anode for the complete water splitting test, and the voltage was only 1.53 V.
[0028] According to the preparation method of Example 1, the molar ratio of Co to Cu was changed to prepare Co 0.50 Cu 0.50 P.Co 0.90 Cu 0.10 P.Co 0.94 Cu 0.06 P.Co 0.97 Cu 0.03 P electrocatalyst, and the electrocatalytic performance of CoP electrocatalyst was also tested under HER reaction and OER reaction. Figure 4 and Figure 5 shown. Figure 4 According to the preparation method of Example 1, the LSV curve of the HER reaction is obtained by adjusting the Cu doping amount ( Figure 4 a), 10 mA cm -2 Comparison of overpotentials between Pt / C / CC, CoP / CC, Cu3P / CF and CC at different current densities ( Figure 4 b) and Co with different Cu contents x Cu 1-x Comparison of overpotential of P / CC ( Figure 4 c), and the Nyquist plot ( Figure 4 d). Figure 4 a confirmed that with the increase of Cu content, the electrocatalytic HER activity first increased and then decreased. When x = 0.95, the catalytic activity was the highest, indicating that appropriate Cu doping can improve the catalytic activity of CoP. Figure 4 b shows that when x = 0.95, the overpotential reaches a minimum of 42 mV, which is significantly smaller than that of Pt / C / CC, CoP / CC, Cu3P / CF and CC, reflecting the best HER activity. Figure 4 c indicates Co 0.50 Cu 0.50 P.Co 0.83 Cu 0.17 P.Co 0.90 Cu 0.10 P.Co 0.94 Cu 0.06 P and Co 0.97 Cu 0.03 The overpotential of P is 164 mV, 150 mV, 116 mV, 50 mV, and 81 mV, indicating that with the decrease of Cu content, the overpotential first decreases and then increases, reaching the minimum at x=0.95. Figure 4 d shows that compared with other catalysts, Co 0.95 Cu 0.05 The charge transfer resistance Rct value of P is smaller, indicating that copper doping increases the charge transfer rate and improves the reaction activity of HER.
[0029] Figure 5 According to the preparation method of Example 1, the LSV curve of the OER reaction is adjusted by adjusting the amount of Cu doping ( Figure 5 a), 10 mA cm -2 Comparison of overpotentials between Pt / C / CC, CoP / CC, Cu3P / CF and CC at different current densities ( Figure 5 b) and Co with different Cu contents x Cu 1-x Comparison of overpotential of P / CC ( Figure 5 c), and the Nyquist plot ( Figure 5 d). Figure 5a It is confirmed that with the increase of Cu content, the electrocatalytic OER activity first increases and then decreases. When x = 0.95, the catalytic activity is the highest, indicating that appropriate Cu doping can improve the catalytic activity of CoP. Figure 5 b shows that when x = 0.95, the overpotential reaches a minimum of 227 mV, which is significantly smaller than Pt / C / CC, CoP / CC, Cu3P / CF and CC, reflecting the best HER activity. Figure 5 c indicates Co 0.50 Cu 0.50 P.Co 0.83 Cu 0.17 P.Co 0.90 Cu 0.10 P.Co 0.94 Cu 0.06 P and Co 0.97 Cu 0.03 The overpotentials of P are 260 mV, 270 mV, 290 mV, and 320 mV, indicating that with the decrease of Cu content, the overpotential first decreases and then increases, reaching the minimum at x = 0.95. Figure 5 d shows that compared with other catalysts, Co 0.95 Cu 0.05 The smaller charge transfer resistance Rct value of P indicates that copper doping increases the charge transfer rate and improves the reaction activity of OER.
[0030] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A superhydrophilic / superaerophobic electrocatalyst Co-Cu-P for overall water splitting, characterized in that: The molecular formula of the electrocatalyst Co-Cu-P is Co x Cu 1-x P, 0≤x<1, the structure is sea urchin-like nanoflower or granular pearl ball.
2. The super-hydrophilic / super-aerophobic electrocatalyst Co-Cu-P for overall water splitting according to claim 1, characterized in that: The electrocatalyst Co-Cu-P preferably has a molecular formula of Co 0.95 Cu 0.05 P, the structure is a sea urchin-like nanoflower composed of nanoneedles grown on carbon cloth.
3. A method for preparing a super-hydrophilic / super-aerophobic electrocatalyst Co-Cu-P for overall water splitting, characterized in that: The preparation method comprises the following steps: (1) Dissolve cobalt nitrate hexahydrate, copper nitrate trihydrate, ammonium fluoride, and urea in deionized water and stir at room temperature for 30 min until a transparent mixed solution is formed; (2) transferring the carbon cloth and the mixed solution to a polytetrafluoroethylene reactor for hydrothermal reaction. After the hydrothermal reaction is completed, cooling, washing with deionized water and anhydrous ethanol, and drying to prepare a precursor; (3) Weigh sodium hypophosphite, place the precursor and sodium hypophosphite in a magnetic boat, respectively located upstream and downstream of a tubular furnace, and calcine under argon conditions. After calcination, collect the product to obtain the electrocatalyst Co-Cu-P.
4. The method for preparing the super-hydrophilic / super-aerophobic electrocatalyst Co-Cu-P for overall water splitting according to claim 3, characterized in that: In step (1), the concentration of ammonium fluoride is 0.1-0.2 mol / L, the concentration of urea is 0.15-0.20 mol / L, and the concentration of Co 2+ , Cu 2+ The total concentration of Co-Cu-P is 0.01-0.05 mol / L. The sum of the stoichiometric numbers of Co and Cu in Co-Cu-P is 1. x Cu 1- x The stoichiometric number of Co in P is x=0, 0.50, 0.83, 0.90, 0.94, 0.95, 0.97, 1.
00.
5. The method for preparing the super-hydrophilic / super-aerophobic electrocatalyst Co-Cu-P for overall water splitting according to claim 4, characterized in that: In the step (1), the concentration of ammonium fluoride is preferably 1 mmol / 7.5 mL, the concentration of urea is preferably 11 mmol / 60 mL, and the concentration of Co 2+ , Cu 2+ The total concentration of is preferably 1 mmol / 30 mL, and the molar ratio of Co to Cu is 0.95:0.
05.
6. The method for preparing the super-hydrophilic / super-aerophobic electrocatalyst Co-Cu-P for overall water splitting according to claim 3, characterized in that: The hydrothermal reaction in step (2) is carried out at 100-150° C. for 8-16 h.
7. The method for preparing the super-hydrophilic / super-aerophobic electrocatalyst Co-Cu-P for overall water splitting according to claim 6, characterized in that: The hydrothermal reaction in step (2) is preferably carried out at 120° C. for 12 h.
8. The method for preparing the super-hydrophilic / super-aerophobic electrocatalyst Co-Cu-P for overall water splitting according to claim 3, characterized in that: In the step (3), the molar ratio of sodium hypophosphite to the precursor is 10:
1.
9. The method for preparing the super-hydrophilic / super-aerophobic electrocatalyst Co-Cu-P for overall water splitting according to claim 3, characterized in that: The calcination conditions in step (3) are 1-3°C·min −1 The temperature is raised to 200-500°C at a heating rate and kept at this temperature for 1-2 h.
10. The method for preparing the super-hydrophilic / super-aerophobic electrocatalyst Co-Cu-P for overall water splitting according to claim 9, characterized in that: The calcination conditions in step (3) are preferably 2°C·min −1 The temperature was raised to 300 °C at a heating rate of 100 °C and kept at this temperature for 2 h.
Citation Information
Patent Citations
Preparation method of electric catalyst for acidic fully-decomposed water
CN106694005A